2005
DOI: 10.1021/bi0477586
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of Human SUMO-3 C47S and Its Binding Surface for Ubc9,

Abstract: Small ubiquitin-related modifier SUMO-3 is a member of a growing family of ubiquitin-like proteins (Ubls). So far, four isoforms of SUMO have been identified in humans. It is generally known that SUMO modification regulates protein localization and activity. Previous structure and function studies have been mainly focused on SUMO-1. The sequence of SUMO-3 is 46% identical with that of SUMO-1; nevertheless, functional heterogeneity has been found between the two homologues. Here we report the solution structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 43 publications
1
37
0
Order By: Relevance
“…This linkage strategy is known to be an effective mimic of the native isopeptide linkage between various target proteins and Ub or Smt3 (the yeast homolog of SUMO) (27,32). Furthermore, the SUMO-3 C47S mutation, which was required for selective disulfide formation at the SUMO C terminus, does not lead to observable structural changes (33). Our semisynthetic strategy readily yielded milligram quantities of homogeneous suH4 ss as seen by reversedphase high performance liquid chromatography (RP-HPLC) and ESI-MS (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This linkage strategy is known to be an effective mimic of the native isopeptide linkage between various target proteins and Ub or Smt3 (the yeast homolog of SUMO) (27,32). Furthermore, the SUMO-3 C47S mutation, which was required for selective disulfide formation at the SUMO C terminus, does not lead to observable structural changes (33). Our semisynthetic strategy readily yielded milligram quantities of homogeneous suH4 ss as seen by reversedphase high performance liquid chromatography (RP-HPLC) and ESI-MS (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The dispersion of positive potential of the two proteins also is comparable. In contrast, the surfaces of other modifiers are usually divided roughly into ''acidic'' face and ''basic'' face as in ubiquitin (17)(18)(19). The positive potential region formed by Arg-6, Arg-54, Arg-42, and Arg-72 in ubiquitin is important for its activating and binding.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, crystal structures of the SUMO-conjugating enzyme Ubc9 in complex with SUMO showed that noncovalent interaction between Ubc9 and SUMO also includes the surface covering the EIL (55)(56)(57)(58). However, in contrast to DPP9, Ubc9 does not differentiate between the SUMO paralogs.…”
Section: Eil a Novel Surface For Noncovalent Interactions Of Sumo1-mentioning
confidence: 99%